ANALISIS KINERJA PENYULUH PERTANIAN DALAM KEGIATAN PENYULUHAN PERTANIAN PADI SAWAH DI KELURAHAN BARUGA KECAMATAN BARUGA KOTA KENDARI - Ani Nila Mei; Salahuddin Salahuddin; La Ode Kasno Arif; Edy Syah Mihrad (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2025)
This study aims to analyze the performance of agricultural extension workers in rice field agricultural extension in Baruga Village, Baruga District, Kendari City. The study population consists of 280 active rice farmers participating in agricultural extension programs. The sample size is 28 farmers (10% of the population), selected using simple random sampling. Data analysis employs descriptive statistics to describe the state of the study variables. The results of the study indicate that the performance of agricultural extension officers in rice farming extension in the Amohalo area in Baruga Village, Baruga District, Kendari City, is in the moderate category. Agricultural extension officers in Baruga Village, Baruga District, Kendari City, have demonstrated adequate or moderate performance in the preparation, implementation, and evaluation of rice farming extension.